Environmental factors associated with the incidence of pulmonary tuberculosis - Sakut Putra Hadi Wijaya; Nopia Wati; Emi Kosvianti; Hasan Husin (Institut Citra Internasional, 2026)
The spread of tuberculosis (TB) is believed to be greatly influenced by environmental variables. Lung disease continues to be a public health problem. The objective of this study is to determine how environmental factors, including ventilation, lighting, housing density, and temperature, are associated with the prevalence of pulmonary TB in Sidomulyo. Using a case-control study paradineed gm, an analytical observational study was conducted. The study sample consisted of 21 individuals with pulmonary TB (cases) and 21 residents without TB (controls). Direct observations of housing conditions and structured questionnaire interviews were used to collect data. Bivariate data were analyzed to assess relationships between variables using the chi-square test. The findings showed a strong association between pulmonary TB (p=0.001) and incidence of lighting and housing density (p=0.000). Neither with home temperature (p=0.520).or ventilation (p=1.000). Based on these findings, public education on the importance of maintaining a healthy home environment, particularly regarding ventilation, lighting, and appropriate housing density, is recommended, in accordance with Ministry of Health guidelines year 2023.